Phase Noise Distortion Compensation in the FMCW Radar Based on Oppositely Modulated Double Chirps - Tschapek, Peter; Fenske, Patrick; Vossiek, Martin (2024 21st European Radar Conference (EuRAD), 2024)
In coherent continuous-wave (CW) radar systems, such as frequency-modulated CW (FMCW) radar systems, phase noise significantly limits both the maximum detectable measurement range and the measurement precision for targets at long range. Approaches that minimize the amount of phase noise during signal generation have so far only led to a marginal improvement of radar systems, and are therefore unsuitable for targets over long range. This paper presents a fundamentally different approach based on full phase noise compensation, achieved by simultaneously emitting two FMCW chirps in opposite directions and then offsetting the beat frequencies. This approach was simulated and verified through measurement using an FMCW primary radar system up to the sensitivity limit of the measurement setup. The metric used was the range precision. Targets were created over ranges of 76-880 m with an analog fiber optical link. The experimental verification results showed an improvement in range precision by a factor of 43. This oppositely frequency-modulated continuous-wave (OFMCW) approach can enable high precision and low-noise measurements for future radar systems.
CRIS-Team Scopus Importer:2024-12-13
Keywords: FMCW; phase noise; phase noise compensation; phase noise modeling; radar system